STRESS AND QUALITY OF LIFE AMONG FATHERS OF SPECIAL NEEDS CHILDREN IN KLANG VALLEY (Journal of Pharmaceutical Negative Results, 2022)
Many research articles have studied the conflicts and stress experienced by parents and mothers of special needs children with different disability such as autism, cerebral palsy, learning disabilities, down syndrome and others. Unfortunately, there are lack of study focusing the experiences of Malaysian fathers of special needs children. This study aimed to examine the stress level using Parental Stress Scale (PSS) and quality of life (QOL) using WHOQOL-BREF, a short version of QOL and to study correlation between stress and quality of life. Two hundred and fifty-six (n=256) samples included fathers of special needs children (n=128) and fathers of typical children (n=128) were recruited into this cross-sectional study from centers or schools in Klang Valley. A set of questionnaire containing 3 sections were distributed via hard copies and online survey. Section 1 comprised father’s demographic data and child’ demographic data and Section 2 was a questionnaire Parental Stress Scale (PSS) to assess stress of fathers and Section 3 was WHOQOL-BREF questionnaire to examine the quality of life of fathers. The demographic data, PSS score and WHOQOL score was analysed using descriptive analysis. Meanwhile, Pearson r was used to identify the correlation between stress and quality of life of fathers of special needs children. The findings of the study showcased that fathers of special needs children have higher mean stress level (M=44.50) and lower quality of life (M=14.16) and where else, fathers of typical children has lower stress level (M=39.70) and higher quality of life (M=15.41). The Person r correlation test indicated moderate negative correlation between stress and quality of life (QOL) of fathers of special needs children, r= .328, p<0.01, two-tailed, n=128. Higher parental stress indicated lower level of sensitivity and poorer quality of parental-child relationship.